Update on Biology of Cutaneous T-Cell Lymphoma - Phyo, Zaw H.; Shanbhag, Satish; Rozati, Sima (Frontiers in Oncology, 2020)
Cutaneous T cell lymphomas (CTCL) comprise of a heterogeneous group of non-Hodgkin lymphomas derived from skin-homing T cells. Variation in clinical presentation and lack of definitive molecular markers make diagnosis especially challenging. The biology of CTCL remains elusive and clear links between genetic aberrations and epigenetic modifications that would result in clonal T cell expansion have not yet been identified. Nevertheless, in recent years, next generation sequencing (NGS) has enabled a much deeper understanding of the genomic landscape of CTCL by uncovering aberrant genetic pathways and epigenetic dysregulations. Additionally, single cell profiling is rapidly advancing our understanding of patients-specific tumor landscape and its interaction with the surrounding microenvironment. These studies have paved the road for future investigations that will explore the functional relevance of genetic alterations in the progression of disease. The ultimate goal of elucidating the pathogenesis of CTCL is to establish effective therapeutic targets with more durable clinical response and treat relapsing and refractory CTCL.